Endothelial function, arterial stiffness and adherence to the 2010 Dietary Guidelines for Americans: a cross-sectional analysis. Issue 11 (17th April 2015) - Sauder, Katherine A.; Proctor, David N.; Chow, Mosuk; Troy, Lisa M.; Wang, Na; Vita, Joseph A.; Vasan, Ramachandran S.; Mitchell, Gary F.; Jacques, Paul F.; Hamburg, Naomi M.; West, Sheila G.
Abstract : Endothelial dysfunction and arterial stiffness are early predictors of CVD. Intervention studies have suggested that diet is related to vascular health, but most prior studies have tested individual foods or nutrients and relied on small samples of younger adults. The purpose of the present study was to examine the relationships between adherence to the 2010 Dietary Guidelines for Americans and vascular health in a large cross-sectional analysis. In 5887 adults in the Framingham Heart Study Offspring and Third Generation cohorts, diet quality was quantified with the 2010 Dietary Guidelines Adherence Index (DGAI-2010). Endothelial function was assessed via brachial artery ultrasound and arterial stiffness via arterial tonometry. In age-, sex- and cohort-adjusted analyses, a higher DGAI-2010 score (greater adherence) was modestly associated with a lower resting flow velocity, hyperaemic response, mean arterial pressure, carotid–femoral pulse wave velocity (PWV), and augmentation index, but not associated with resting arterial diameter or flow-mediated dilation (FMD). In multivariable models adjusting for cardiovascular risk factors, only the association of a higher DGAI-2010 score with a lower baseline flow velocity and augmentation index persisted (β = − 0·002, P = 0·003 and β = − 0·05 ± 0·02, P < 0·001, respectively). Age-stratified multivariate-adjusted analyses suggested that the relationship of higher DGAI-2010 scores with lower mean arterial pressure, PWV and augmentation index was more pronounced among adults younger than 50 years. Better adherence to the 2010 Dietary Guidelines for Americans, particularly in younger adults, is associated with a lower peripheral blood flow velocity and arterial wave reflection, but not FMD. The present results suggest a link between adherence to the Dietary Guidelines and favourable vascular health.